Leveraging Interactive Mobile Technologies for Enhanced Learning Outcomes A Systematic Review - Kumar, Ravi; Sharma, Priya (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The growing integration of mobile technologies has reshaped how learning is designed, experienced, and evaluated in modern education. This systematic review synthesizes findings from 78 empirical studies published between 2015 and 2024 to examine how interactive mobile tools—such as adaptive systems, simulations, gamification, and augmented reality—affect measurable learning outcomes. The analysis followed the PRISMA framework and focused on peer-reviewed research that employed experimental or quasi-experimental designs. Results indicate that mobile learning yields moderate yet consistent improvements in knowledge acquisition, motivation, and skill development, with stronger effects observed in STEM and health-related subjects. Adaptive systems and simulation-based applications were found to be the most effective, while gamification and augmented reality produced mixed outcomes depending on instructional design quality. The review also reveals that pedagogical alignment, teacher readiness, and institutional support play a decisive role in determining success. Technology by itself does not ensure learning gains; rather, meaningful results arise when digital tools are purposefully embedded into curriculum design and supported through professional training. Despite methodological and contextual limitations in existing studies—such as short intervention durations and limited geographic diversity—the evidence supports a cautiously optimistic view: mobile learning can complement traditional instruction when guided by sound pedagogy, coherent assessment strategies, and equitable access.